2023
DOI: 10.1128/spectrum.01284-23
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Liver-Expressed Shiftless Is an Evolutionarily Conserved Antiviral Effector Restricting Human and Murine Hepaciviruses

Abstract: Viruses have evolved ways to evade or blunt innate cellular antiviral mechanisms within their cognate host species. However, these adaptations may fail when viruses infect new species and can therefore limit cross-species transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…This indicated that zinc-finger domain might play important role in SHFL location. Recently, Shfl was also reported to own the anti-HCV ability in mouse model ( Zhang et al, 2023 ). These studies suggest SHFL could effectively inhibit viruses in flavivirus family.…”
Section: The Inhibiting Function Of Shfl To Rna Virusesmentioning
confidence: 99%
“…This indicated that zinc-finger domain might play important role in SHFL location. Recently, Shfl was also reported to own the anti-HCV ability in mouse model ( Zhang et al, 2023 ). These studies suggest SHFL could effectively inhibit viruses in flavivirus family.…”
Section: The Inhibiting Function Of Shfl To Rna Virusesmentioning
confidence: 99%